Synthesis, Structural Characterization, and Catalytic Property of A Zn(II) Complex with 5-Bromosalicylaldehyde Ligand - Xi Shi Tai; Peng Fei Li; Xin Wang; Li Li Liu (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2017)
The study on catalytic activity of complex materials has been one of the hot spots in coordination chemistry. In order to extensively study the catalytic activity of complexes, a new six-coordination Zn(II) complex material, [ZnL2(H2O)2] (C1) (HL = 5-bromosalicylaldehyde), has been prepared with 5-bromosalicylaldehyde, NaOH, and Zn(CH3COO)2·2H2O as raw materials. The structure of C1 was determined by elemental analysis, IR spectra, and single crystal X-ray diffraction. The Zn(II) complex shows a moderate catalytic activity for A3 coupling reaction of benzaldehyde, piperidine, and phenylacetylene with the benzaldehyde conversion reached 54.6 %. Furthermore, the Zn(II) complex catalyst exhibited 54.8 %, 53.8 %, and 54.4 % conversions of benzaldehyde in the second, third, and fourth cycles, respectively. In addition, the Zn(II) complex features a selectivity of 100 % to the product of propargylamine for the A3 coupling reaction.